Yo-Yo intermittent recovery test level 2 and its relationship with other typical soccer field tests in female collegiate soccer players - Lockie, R. G.; Jalilvand, F.; Moreno, M. R.; Orjalo, A. J.; Risso, F. G.; Nimphius, S. (The Journal of Strength and Conditioning Research, 2017)
The ability to complete high-intensity running is essential for soccer. The Yo-Yo Intermittent Recovery Test Level 2 (YYIRT2) can measure this capacity, but there is limited information regarding this assessment in collegiate female soccer players. This study investigated the YYIRT2 as a measure of high-intensity running in this population, and its relationship to other soccer field tests. Twenty-one players from a Division I team were recruited. In addition to the YYIRT2, subjects completed linear (0-5, 0-10, and 0-30 m sprint intervals) and change-of-direction (pro-agility and 60-yard shuttle) speed tests, as well as the YYIRT Level 1 (YYIRT1), to assess relationships with YYIRT2 by correlations (p = 0.05). The correlation of YYIRT1 with the speed tests was also assessed. The YYIRT1 and YYIRT2 were standardized using z-scores for comparison with elite benchmarks to investigate relative performance on each test. The YYIRT2 and YYIRT1 distances did not significantly correlate with those of the speed tests (r = -0.251 to 0.274). There was a large relationship between YYIRT2 and YYIRT1 distances (r = 0.582), although the explained variance was low (33.87%). Mean YYIRT2 z-scores (-4.29 ± 1.66) indicated a performance further from elite benchmarks than those of the YYIRT1 (-1.92 ± 1.61), and 90.5% (19 of 21) subjects performed relatively better in the YYIRT1 than YYIRT2. The YYIRT2 provided a more specific measure of high-intensity running to that of the YYIRT1 in collegiate female soccer players. Coaches may consider using the YYIRT2 to gauge and track progress of high-intensity running capabilities and create training programs to improve this ability in female players.